Penetration mechanism of dimethyl sulfoxide in human and pig ear skin: An ATR–FTIR and near-FT Raman spectroscopic in vivo and in vitro study. Issue 5 (2008) - Greve Greve, Tanja M. Tanja M.; Andersen Andersen, Kristine B. Kristine B.; Nielsen Nielsen, Ole F. Ole F.
Abstract : The penetration mechanism of dimethyl sulfoxide (DMSO) in human skin in vivo and in vitro and pig ear skin in vitro was studied using attenuated total reflectance (ATR) Fourier transform (FT) infrared (IR) and near-FT-Raman spectroscopy. The results showed changes in the conformation of the skin keratins from an α-helical to a β-sheet conformation. These changes were proved to depend on the concentration of free water in the sample as DMSO tended to bind to free water before the protein-bound water was replaced and the protein conformational changes were induced. The induced conformational changes were shown to be completely reversible as the proteins are returned to their original state within 20 h after the treatment with DMSO. The penetration depth of DMSO was shown to depend on the time of exposure – however, after only 15 min DMSO has penetrated the stratum corneum, which is the skin barrier.